Osmotic dehydration kinetics of oyster mushroom - Yasmin, S; Islam, MN; Alim, MA; Kamal, MS (Journal of the Bangladesh Agricultural University, 2017)
This research was carried out to study the effect of osmotic dehydration behavior of oyster mushroom. The effect of solution concentration, immersion time and temperature on mass transfer parameters were observed during osmotic dehydration of oyster mushroom at three different temperatures −12, 27 and 45°C. A number of process parameters on osmotic dehydration such as water loss (WL), solid gain (SG), and normalized solid content (NSC) were investigated. Results showed that increase in salt concentration and immersion time resulted in %WL, %SG and NSC. The highest NSC (4.09 g solids/100g of initial weight of sample) was achieved for product osmosed in 25% salt solution for 6 hr immersion time. The pseudo diffusion coefficient, k was determined by using Fick’s First Law of diffusion equation. Plotting k values against inverse absolute temperature an Arrhenius type relationship was developed from which the calculated activation energy values of 1.8 and 3.64 kcal/gm-mole were obtained for 20% and 15% salt solution respectively.